PHRASEOLOGICAL UNITS WITH THE CONCEPT KNOWLEDGE IN ENGLISH AND THEIR MEANING (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article analyzes phraseological units with the concept knowledge in English and their content in the English language.